A new overview on rare earth diphenylphosphinates: Europium characteristic luminescence of low dimensional nanostructured materials - Bim, Luís F. Bricks [UNESP]; Stucchi, Elizabeth B. [UNESP]; Cebim, Marco A. [UNESP] (Elsevier, 2018)
Porous crystalline luminescent polymer compounds have attracted huge interest due to their supramolecular structures, aesthetically attractive structural topologies and potentialities for innovative technological applications. However, wet route precipitation or hydro/solvothermal methods may lead to the formation of highly insoluble porous coordination networks, as is true of europium diphenylphosphinates – [Eu(dpp)3]n. The aim of this work was to study the optical behavior and its relation to the structure of [Eu(dpp)3]n complexes obtained through different synthetic approaches by precipitation: wet route (WRS), ultrasound-assisted wet route (U-WRS), modulator-assisted wet route (M-WRS) and wet route synthesis with solvothermal treatment (S-WRS). These methodologies allowed to synthetize crystalline materials in which both chelate and bridged coordination modes coexist, and they were efficient for obtaining stick-shaped 1D1 nanostructured materials with well-defined optical properties. Changes in precipitation kinetics and crystalline phases formation rate led to a distribution of Eu3+ ions in higher symmetry sites (HSS). S-WRS, transforming part of the less symmetrical sites into HSS, provided a better ordering of [Eu(dpp)3]n. Furthermore, this is the first report of two or more symmetry sites for Eu3+ in a pure [Eu(dpp)3]n matrix.
Keywords: Coordination compounds; Coordination polymers; Lanthanides; Metal-organic frameworks; Nanowires; Photoluminescence spectroscopy